Correlation factor innovation and economic growth in innovation theory of cyclic economic development Joseph Schumpeter - Stepanova A. (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The influence of innovation factor on economic growth of countries at different stages of economic cycle. The role ofinnovation in overcoming the economic crisis.